UNDERSTANDING THE CONCEPT OF DIGITAL LITERACY AND INNOVATIVE WORK BEHAVIOR - Hani Maisarah Nasaruddin; Muhamad Aiman Najmi bin Zulkifli; Faris Harith bin Badrul Hisham Nasution; Nurazzaratul Arissa binti Ab Halim; Nur Zawani binti Zailudin (International Journal of Accounting, Finance and Business, 2022)
In the present circumstances, coronavirus disease (COVID-19), which limits themovement to go to work, has the potential to open up everyone's attention to the use of moretechnological innovations. Other than that, especially office employees use their abilities toadapt to these changes even though this new norm situation could not have physical touch. Thepresence of the virus COVID-19 that hinders movement is an issue. One of the difficultproblems is acquiring the necessary digital literacy for success in employment. Therefore, thisresearch aims to explore the concept of digital literacy and innovative work behavior in aworkplace setting. This study provides a clear understanding of digital literacy, personalinnovativeness, and individual innovative work behavior. In addition, the current study involvesreviewed research articles that were gathered from Scopus, Science Direct, and Emeralddatabases. A total of 15 articles have been reviewed from the year 2017 to 2022. Based on thereview, this study found that employee digital literacy is on the rise due to the current changesin the modern era. In addition to that, past studies revealed that digital literacy is widelyassociated with innovative work behavior. This study's findings contribute to the body ofliterature on digital literacy and assist organizations in understanding the importance of digitalliteracy on organizational outcomes such as innovative work behavior and organizationalperformance. The digital literacy program will provide employees with the digital skillsrequired to engage in innovative work behavior. Future studies are recommended to provideempirical evidence on the association between digital literacy and innovative work behavior.